口腔内アプローチによる骨間隙形成と有茎頰脂肪体を用いた顎関節授動術の1例 - 金子, 一朗; 大迫, 里江; 金山, 純一; 管野, 貴浩; 辰巳, 博人; 成相, 義樹 (日本口腔外科学会雑誌, 2020)
We report the use of bony gap arthroplasty to treat temporomandibular joint (TMJ) ankylosis via an intraoral approach using a surgical saw and a pedicled buccal fat pad affording interpositional grafting. A 42-year-old man had severe trismus attributable to TMJ ankylosis caused by an accident at work. Surgery proceeded under general anesthesia induced via nasal intubation. We created an incision at the anterior border of the mandibular ramus and external oblique ridge. After elevation of a mucoperiosteal ramus flap and resection of the coronoid process, a bone gap of about 10 mm was created using a surgical saw. The gap was filled with a pedicled buccal fat pad sutured to the medial pterygoid muscle. Aggressive mouth-opening training commenced on postoperative day 3. The advantages of our technique include a clear intraoral surgical field and simple harvesting of the graft material within the same field. Five years after operation, the extent of mouth-opening was 34 mm, and the postoperative clinical outcome remains favorable.